2012
DOI: 10.1103/physrevb.86.035212
|View full text |Cite
|
Sign up to set email alerts
|

Polarization anisotropy of charge transfer absorption and emission of aligned polymer:fullerene blend films

Abstract: An improved understanding of the electronic structure of interfacial charge transfer (CT) states is of importance due to their crucial role in charge carrier generation and recombination in organic donor-acceptor (DA) solar cells. DA combinations with a small difference between the energy of the CT state (E CT ) and energy of the donor exciton (E D * ) are of special interest since energy losses due to electron transfer are minimized, resulting in an optimized open-circuit voltage. In that case, the CT state c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 48 publications
2
46
1
Order By: Relevance
“…subsequently free charge carriers. 17,19,21 Moreover, the fluorescence spectrum of blend films contains, in contrast to neat films, an additional red-shifted band, which has been assigned to emission of the interfacial CT state. 21 The spin-casting procedure resulted in a random organization of the TQ1 polymer phase within the film plane, and thus, we denote these films as isotropic.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…subsequently free charge carriers. 17,19,21 Moreover, the fluorescence spectrum of blend films contains, in contrast to neat films, an additional red-shifted band, which has been assigned to emission of the interfacial CT state. 21 The spin-casting procedure resulted in a random organization of the TQ1 polymer phase within the film plane, and thus, we denote these films as isotropic.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…Forster radius is proportional to the 6th power root of the oscillator strength (dipole moment squared) of the acceptor multiplied by the fluorescence quantum yield of the donor, where both the donor and acceptor are emissive CT states. By comparing the CT and polymer (TQ1) absorption of blends with low polymer concentration, the average oscillator strength of a CT state has been estimated to be about 1/300 of the oscillator strength of the TQ1 spectroscopic unit, 21 which is consistent with calculations on other polymer:fullerene systems. 26,27 Note that this estimation gives the oscillator strength averaged over all CT states (emissive and nonemissive), while emissive CT states probably have much larger oscillator strengths than those which undergo ultrafast charge separation on subpicosecond time scale.…”
Section: Chemistry Of Materialsmentioning
confidence: 84%
“…25,36 It was shown that electron-transfer process demonstrates a noticeable conservation of the polarisation memory due to the correlation between the excitonic, CT and polaronic transition dipoles of the polymer. [37][38][39][40] In contrast, the polarization of the fullerene excitation has little correlation with the polarization of the polymer's polaronic transition, and thus the anisotropy following hole transfer will be negligibly low.…”
Section: 31mentioning
confidence: 99%
“…6 In addition, alignment of the polymer chains in an OPV cell may provide insight into energy conversion processes. 11 There have been a number of techniques used to uniaxially align conjugated polymer films that have focused on alignment of homogeneous polymer systems. 4,7,[12][13][14] In polymer:fullerene blends, such as poly(3-hexylthiophene): Phenyl-C61-butyric acid methyl ester (P3HT:PCBM), alignment of the P3HT component has recently been demonstrated by (1) mechanically rubbing the film at an elevated temperature (150 C) 6 and (2) through directed crystallization.…”
mentioning
confidence: 99%